Language Games In Learning Arabic Rhetoric For Non- Arab/ الألعاب اللغوية في تعلم البلاغة العربية للناطقين بغير العربية - Mohammad Saleh; Zamri Arifin; Lily Hanefarezan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Non-native speakers of the Arabic language face various problems in learning Arabic rhetoric, including that the traditional lesson may be devoid of the motivation and enjoyment that the learner needs, which has the most significant impact on raising the level of accuracy and linguistic fluency, so it was necessary to employ means that the learners desire to overcome these problems. One of those means is language games. This research aimed to reveal the effect of using language games in learning Arabic rhetoric among learners of Arabic language of other languages from their point of view. Also, describe the evaluation of their impressions and monitor their perceptions towards employing language games in their learning. The research adopted the quantitative approach using the questionnaire tool, and a questionnaire Bicen Kocakoyun translated into Arabic was adopted in the study of Aboukhateta. This questionnaire consisted of twenty-seven questions according to the five-year Likert scale, and it included three axes: the impact of language games on mastering Arabic rhetoric from the student's point of view, evaluating students' impressions of language games, and monitoring their perceptions about language games in learning Arabic rhetoric. This questionnaire was distributed to thirty Malaysian students of Arabic-speaking non-native speakers at Yarmouk University in a purposeful manner. The research results showed that non-native Arabic language learners see a significant impact of using language games in learning Arabic rhetoric and that these learners have good impressions and perceptions about employing language games in learning Arabic rhetoric.